Synapses as Therapeutic Targets for Autism Spectrum Disorders: An International Symposium Held in Pavia on July 4th, 2014 - Curatolo, Paolo; Ben-Ari, Yehezkel; Bozzi, Yuri; Catania, Maria Vincenza; D’Angelo, Egidio; Mapelli, Lisa; Oberman, Lindsay M.; Rosenmund, Christian; Cherubini, Enrico (Frontiers in Cellular Neuroscience, 2014)
New progresses into the molecular and cellular mechanisms of Autism Spectrum Disorders (ASDs) have been discussed in one day International Symposium held in Pavia (Italy) on July 4th, 2014 entitled "Synapses as therapeutic targets for Autism Spectrum Disorders" (satellite of the FENS Forum for Neuroscience, Milan 2014). In particular, world experts in the field have highlighted how animal models of ASDs have greatly advanced our understanding of the molecular pathways involved in synaptic dysfunction leading sometimes to "synaptic clinical trials" in children.